(untitled) (SCIÉNDO INGENIUM, 2021)
The present research aimed to show some results of conditions of existence and uniqueness and examples on the solution of fractional differential equations, showing with them different solution methods. For this, some general aspects of definitions and basic results of the fractional calculation are presented.